Role of Educational Institute in Heritage Management: A Case Study in the Lalmai-Mainamati Hill Region, Bangladesh - Hassan, Md Nazmul; Md. Sadequzzaman (CenRaPS Journal of Social Sciences, 2023)
This paper aims to investigate the role of educational institutes in heritage management from the local and national policy level to safeguard archaeological heritage perspectives in the Lalmai-Mainamati area, cumilla, Bangladesh. Lalmai-Mainamati area is one of the historical places in Bangladesh and in this area almost 50 archaeological sites were marked by the department of archaeology (DOA), and most of the sites represent our historical remains from 9th to 12 century BC. The Department of archaeology maintained all of these sites under antiquity act 1968 but the drawback of manpower resources and financial budget is that most of the sites are unprotected and lack proper maintenance process. Local people, tourists, Fanatic society, and mischievous people are ruining our historical past evidence in many ways. From the causes of these casualties, people are not aware of it and they are not realizing the importance of our heritage practicing and safeguarding lack of proper information & instruction when they visit these historical places or are attached somehow with these archaeological sites. This paper deals with how our educational institute can play a vital role in safeguarding archaeological heritage in many ways perspectives on the Lalmai-Mainamati area.